2022
DOI: 10.3389/fvets.2022.819082
|View full text |Cite
|
Sign up to set email alerts
|

Feline Heartworm in Clinical Settings in a High Canine Prevalence Area

Abstract: Heartworm (HTW) infection in cats is associated with persistent pulmonary pathology, even when clinical signs are absent. Treatment options for cats are limited once infected, making prevention an important topic for discussion with cat owners. In Brazil, tests to detect feline HTW infections are unavailable, likely leading to an underestimation of its impact on the wellbeing of cats. The present study investigated the seroprevalence of HTW antigen in cats living in an area with high canine HTW prevalence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Similarly, in this study it is observed that the antibody seroprevalence of D. immitis in FeLV positive cats is significantly higher. These results contradict previous publications, which indicate a lack of relationship between positivity to feline viruses and the presence of heartworm ( 3 , 15 , 30 ). Although it could be theorized that the immunosuppression caused by these feline pathologies could favor D. immitis infection, it is necessary to carry out more studies to confirm this.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, in this study it is observed that the antibody seroprevalence of D. immitis in FeLV positive cats is significantly higher. These results contradict previous publications, which indicate a lack of relationship between positivity to feline viruses and the presence of heartworm ( 3 , 15 , 30 ). Although it could be theorized that the immunosuppression caused by these feline pathologies could favor D. immitis infection, it is necessary to carry out more studies to confirm this.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the distribution is well studied in the canine species, there is an important lack of knowledge in the cat; in Spain, there are only published epidemiological studies in the Canary Islands, Madrid, Barcelona and Zaragoza ( 10 14 ). However, it is estimated that where canine heartworm is present, feline heartworm disease is also present ( 15 , 16 ). Therefore, the objective of this study was to complete the epidemiological puzzle of feline heartworm in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of feline heartworm seroprevalence is limited; the Companion Animal Parasite Council reported 0.57% seroprevalence in the United States and 1.43% seroprevalence in Canada for 2022 [ 24 ]. Another 2022 study found a heartworm antigen prevalence of 1.2% in Rio de Janeiro, Brazil [ 25 ]. One recent study found a similar prevalence of heartworm in cats to the prevalence in high-risk dogs when using antigen and antibody testing in parallel [ 26 ].…”
Section: Introductionmentioning
confidence: 99%